Pengembangan Media Pembelajaran (Online) Berbantuan Aplikasi Kahoot Dan Komik Strip Dalam Upaya Meningkatkan Nilai Kognitif Siswa Kelas VIII SMPK ST. Fransiskus Asisi Samarinda - Purwanti, Nuryanti; Maasawet, Elsje Theodora; Rambitan, Vandalita M. M. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The research was aimed to know the early diagnose toward students learning ability and the process condition of teaching and learning which were basis of the development science media learning which capable to increase cognitive learning value of students grade VIII SMPK. The purpose of research were: (1) to assist the lack of accomodation of earlier media learning, (2) to create online media learning in using kahoot and comic strip application, (3) to product yield was worth to examined by validator and students respondence due to development testing to increase integrated science comprehension for students grade viii with score amount 3,76 and 3.24 and, (4) the last result of the product were effective to increase cognitive value for students of SMP grade VIII. As a result of learning, which prove by pretest average score amount 55,3, then up to 84,2 after post test. the comparation t count for t table amont 2,283 > 1,99897 and independent test t amount  0,026 < 0,05. These were prove thhat media learning capable to increase cognitive value for science subject of students grade VIII SMPK st, fransiskus Asisi samarinda. Therefore the evaluation media learning which developed was deserve to used by students of SMP grade VIII In Samarinda.